Hubungan Enzim Hepar SGOT dan SGPT pada Pasien Diabetes Mellitus Tipe 2 - Dewi, Novita; Supriyadi, Supriyadi (Universitas Baiturrahim, 2024)
Diabetes mellitus is a collection of metabolic symptoms starting with insulin secretion or insulin resistance. Insulin resistance in Type 2 Diabetes Mellitus (T2DM) sufferers causes a decrease in the absorption of glucose levels. The liver cytosol is a source of glucose energy obtained from fatty acid synthesis. This synthesis event causes